Synthesis of Comb-Polyurethane-Modified Polycarboxylate at Indoor Temperature and Its Interaction With Portland Cement - Xiang, Shuncheng; Tan, Yansheng; Gao, Yingli (Frontiers in Materials, 2021)
According to the principle of radical polymerization reaction, different polycarboxylates with comb structure were synthesized. With the other two commercial polycarboxylates (C-PCE-1 and C-PCE-2), the effects of all the polycarboxylates on adsorption, hydration, zeta potential, liquid surface tention and flowability in Portland cement were determined. Compared to O-PCE and C-PCEs, the adsorption value of M-PCE increased by 14.1% and the adsorption rate increased by 24% in max. O-PCE, C-PCE-1 and C-PCE-2 have a delayed effect on the hydration of the cementitious materials, but M-PCE does not. Due to higher adsorption amount, M-PCE with siloxane groups has an excellent comprehensive performance of zeta potential, liquid surface tention and flowability in cementitious materials.